Exploring the alignment between clinician-reported assessment of social autonomy and patient-reported assessment of quality of life in mood disorders: a cross-sectional study - Fraichot, Alexandre; Favre, Sophie; Jermann, Françoise; Richard-Lepouriel, Hélène (Frontiers in Psychiatry, 2025)
IntroductionPatient-reported quality of life reflects subjective factors such as well-being and autonomy, while clinicians may focus on functional capabilities. Understanding the factors behind the alignment or discordance between these assessments can help comprehend patients’ values and social contexts.MethodsThis study explored the agreement between clinician-reported assessment of social autonomy and patient-reported assessment of quality of life in 92 adult participants with a mood disorder. Validated scales were used to measure the severity of depression, hypomania, quality of life, social autonomy, and internalized stigma.ResultsSociodemographic and clinical variables were compared between different groups using ANOVAs and chi-square tests. The results indicated that individuals with good social autonomy and quality of life had lower self-stigma scores. Those with low social autonomy and quality of life were less likely to be employed. The group with discordant scores between social autonomy and quality of life did not significantly differ from the other concordant groups in terms of sociodemographic and clinical variables.DiscussionThe study suggests that mental health professionals should consider the association between clinician-reported and patient-reported assessments and their correlates before tailoring specific interventions.